Helicopter parenting instrument: estudos psicométricos iniciais com adultos emergentes - Borges, D.; Portugal, A.; Magalhães, E.; Sotero, L.; Lamela, D.; Prioste, D. (Revista Iberoamericana de Diagnòstico y Evaluaciòn Psicològica, 2019)
The present study describes validity and reliability evidence of the Helicopter Parenting Instrument (HPI), in the Portuguese context. This instrument evaluates children's perception of inappropriate parental behaviors according to children's developmental stage (e.g., overprotection, decision-making by the children). A total of 187 emerging adults agreed to participate, aged between 18 and 25, answered a socio-demographic questionnaire, HPI, Brief Symptom Inventory (BSI) to assess anxiety and depression; the Family Climate Inventory (ICF) to assess cohesion and conflict, and the Identity Development Dimension Scale (DIDS) to assess identity development. Construct validity evidence was obtained through confirmatory factor analysis, showing an adequate fit to the one-dimensional model, as well as convergent validity evidence was found from the correlations between HPI, BSI, ICF and DIDS. A satisfactory internal consistency value was also found.